FEMORAL HERNIA: UNCOMMON, BUT ASSOCIATED WITH POTENTIALLY SEVERE COMPLICATIONS - COELHO,Julio Cezar Uili (2021)
ABSTRACT Background: Although the laparoscopic access is becoming the preferable treatment for femoral hernia, there are only few studies on this important subject. Aim: To assess the outcomes of the totally extraperitoneal laparoscopic (TEP) access in the treatment of femoral hernia. Methods: Data of 62 patients with femoral hernia who underwent herniorrhaphy were retrospectively reviewed. The diagnosis of femoral hernia was established by clinical and/or imaging exams in 55 patients and by laparoscopic findings in seven. Results: There were 55 (88.7%) females and 7 (11.3%) males, with female to male ratio of 8:1. The mean age was of 58.9±15.9 years, ranging from 22 to 92 years. Most patients (n=53; 85.5%) had single hernia and the remaining (n=9; 14.5%) bilateral, making a total of 71 hernias operated. Prior lower abdominal operations were recorded in 21 (33.9%) patients. Conversion to laparoscopic transabdominal preperitoneal procedure was performed in four (6.5%). Open herniorrhaphy was needed in two (3.2%), one with spontaneous enterocutaneous fistula in the groin region (Richter’s hernia) and the another with incidental perforation of the adjacent small bowel that occurred during dissection of hernia sac. There was no mortality. Conclusion: Femoral hernia is uncommon, and it may be associated with potentially severe complications. Most femoral hernias may be successfully treated with totally extraperitoneal laparoscopic access, with low conversion and complication rates.